Serine Repeat Antigen Peptides which bind specifically to Red Blood Cells. (2000)
It has been reported that serine repeat antigen (SERA) binds directly to human erythrocyte membranes, inside-out vesicles and intact mouse erythrocytes. Similarly, mAbs specific against SERA are effective in blocking red blood cell (RBC) invasion by P. falciparum merozoites. Furthermore, the N-terminal recombinant SERA fragment inhibits the merozoite invasion of erythrocyte. In this study of 49 non-overlapping 20-residue-long peptides encompassing the whole SERA protein FCR3 strain, seven peptides having high RBC binding activity were found. Six of these peptides (three from the SERA N-terminal domain) are located in conserved regions and show affinity constants between 150 and 1100 nM, Hill coefficients between 1.5 and 3.0 and 30 000–120 000 binding sites per cell. Some of these peptides inhibited in vitro merozoite invasion of erythrocyte and intra-erythrocytic development. Residues which are critical in the binding to erythrocytes (in bold face), i.e. 6725 (YLKETNNAISFESNSGSLEKK), 6733 (YALGSDIPEKCDTLASNCFLS), 6737 (YDNILVKMFKTNENNDKSELI), 6746 (DQGNCDTSWIFASKYHLETI), 6754 (YKKVQNLCGDDTADHAVNIVG) and 6762 (NEVSERVHVYHILKHIKDGK), were determined by means of competition assays with high-binding peptide glycine analogues. The identification of peptides which bind to erythrocyte membrane is important in understanding the process of RBC invasion by P. falciparum merozoites.